THU0078 EXPRESSION PROFILE ANALYSIS OF LONG NONCODING RNAS INDUCED BY IL-1ß IN RHEUMATOID ARTHRITIS FIBROBLAST-LIKE SYNOVIOCYTES. (2nd June 2020) - Kim, J. M.; Kang, H. J.; Jung, S. J.; Song, B. W.; Jeong, H. J.; Son, C. N.; Kim, S. H.; Hur, K.
Abstract : Background: Long noncoding RNAs (lncRNAs) have recently emerged as important biological regulators and the aberrant expression of lncRNAs has been reported in various diseases including cancer, cardiovascular disease, and diabetes mellitus. However, the role of lncRNAs in the pathogenesis of rheumatoid arthritis (RA) remains unknown. Objectives: Thus, we studied lncRNAs influenced by IL-1, which is one of the key mediators in the pathogenesis of RA, and also investigated whether regulation of NF-κB activation, which is known to be induced by IL-1, could lead to the changes of expression of those lncRNAs. Methods: Fibroblast-like synoviocytes (FLS) were obtained from the knee joints of the patients with RA. The next-generation sequencing (NGS) data were analyzed to identify differentially expressed lncRNAs between unstimulated RA FLS and IL-1-stimulated RA FLS. The expression levels of the top 5 candidates in NGS data were validated by RT-qPCR using extended number of unstimulated RA FLS and IL-1-stimulated RA FLS. IMD-0560, an inhibitor of IκB kinase (IKK) was used for the regulation of NF-κB activation. Activation and inhibition of NF-κB were confirmed by Western blotting. Changed expressions of the lncRNAs were identified by RT-qPCR. Results: NGS analysis revealed up-regulated 30 lncRNAs and down-regulated 15 lncRNAs in IL-1-treated RA FLS compared with unstimulated RA FLS. Top 5 lncRNAs were selected among 30 lncRNAs up-regulated by IL-1 in RA FLS based on fold-change with P-value cutoff. The up-regulated lncRNAs including NR_046035, NR_027783, NR_033422, NR_003133, and NR_049759 were validated by RT-qPCR. IMD-0560 inhibited phosphorylation of IκBα induced by IL-1 in RA FLS. Overexpression of lncRNAs induced by IL-1 was also inhibited by IMD-0560 in RA FLS. Conclusion: Our study revealed that IL-1 increased the expression of NR_046035, NR_027783, NR_033422, NR_003133, and NR_049759 in RA FLS. In addition, the expression of these lncRNAs was regulated by inhibition of NF-κB activation. Thus, our data suggest that the lncRNAs might be involved in the pathogenesis of RA through NF-κB signaling pathway. References: [1]Long noncoding RNAs and human disease. Trends Cell Biol. 2011 Jun;21(6):354-61. [2]A long noncoding RNA mediates both activation and repression of immune response genes. Science. 2013 Aug 16;341(6147):789-92. [3]Long noncoding RNA expression profile in fibroblast-like synoviocytes from patients with rheumatoid arthritis. Arthritis Res Ther. 2016 Oct 6;18(1):227. Disclosure of Interests: None declared